Dinamika psikologis pada individu dengan trauma masa lalu - Nugroho, Nihlah Alifatul Rohmah (Maliki Interdisciplinary Journal, 2024)
This study investigates the psychological dynamics that people who have previously undergone traumatic events go through. An individual's psychological well-being and mental health can be greatly impacted by past trauma. This research identifies patterns of thoughts, feelings, and actions that arise in reaction to trauma through a qualitative investigation employing in-depth interviews. Important discoveries demonstrate that people who have experienced trauma in the past often exhibit symptoms including melancholy, persistent anxiety, PTSD, and difficulties building interpersonal connections. The research also determined the elements that help or impede the healing process, as well as the coping mechanisms individuals employed to deal with the effects of trauma. The findings of this study may assist mental health professionals create more beneficial therapies for those who have experienced trauma in the past.